PENERAPAN MODEL PEMBELAJARAN GENERATIVE LEARNING PADA PEMBELAJARAN FISIKA DI SMA - Erma Karlina; Singgih Bektiarso; Albertus Djoko Lesmono (FKIP Universitas Jember, 2017)
The research focused on the influence of generative learning to students’s discuccion skill and students’s physics achievement. The purposes of this research are (1) to describe to students’s discuccion skill using generative learning model in learning physics, (2) to examine students’s physics achievement using generative learning model better than using direct instruction model in learning physic. The type of this research is experiment by using randomized post-test only control group design. Sample of the research are X MIPA 3 as an experiment class and X MIPA 4 as an control class. The techniques of data collection are observation, test, documentation, and interview. The techniques of data analysis using descriptive analysis and Independent Sample T-Test by SPSS version 20.. The result of the research are (1) average value students’s discussion skill using generative learning model is 4,2 (2) students’s physics achievement acquired of analytical results Independent-Sample T-test Sig. (1-tailed) of 0,001. The research can be concluded that (1) the students’s discussion skill using generative learning model is in good criteria, (2)the students’s physic achievement using generative learning model better than using direct instruction model in learning physic.